Comparison of Postoperative Pain in Root Canal Treatment by Using Sodium Hypochlorite and Chlorhexidine-based Root Canal Irrigants - Naz, Tabassum; Khan, Irfan Ullah; Khan, Ahsan Ali; Jan, Mashal Zeb; Illiyeen, Momina; Gul, Sidra; Naureen, Tehreema; Ahmed, Suhaib (Biological and Clinical Sciences Research Journal, 2025)
Postoperative pain following root canal treatment remains a common clinical concern and may be influenced by the type of irrigant used during the procedure. Objective: To compare the frequency of postoperative pain observed in root canal treatment by using sodium hypochlorite and chlorhexidine-based root canal irrigants. Methods: This study was conducted on 168 patients diagnosed with irreversible pulpitis in posterior teeth who underwent root canal treatment, and were allocated via lottery into two equal groups. Group A received irrigation with 5.25% sodium hypochlorite, while Group B received 2% chlorhexidine. Postoperative pain was evaluated in both groups using a 10-point Visual Analogue Scale (VAS), with a score of ≥3 indicating significant pain at 45 days after treatment. SPSS 23 was used for analysing the data. Results: Postoperative pain was reported significantly more frequently in the sodium hypochlorite group, with 26 (31.0%) cases experiencing pain, compared with 13 patients (15.5%) in the chlorhexidine group (p=0.01). The incidence of postoperative swelling was 10.7% in Group A and 4.8% in Group B. Postoperative bleeding was observed in 8.3% and 6.0% cases, respectively, in both groups. Conclusion: The present study found that the frequency of pain was lower in root canal treatment with chlorhexidine as the root canal irrigant compared with sodium hypochlorite.